Botanical extracts: alternative control for silverleaf whitefly management in tomato - Baldin, Edson Luiz Lopes [UNESP]; Fanela, Thiago Luis Martins [UNESP]; Pannuti, Luiz Eduardo da Rocha [UNESP]; Kato, Massuo J.; Takeara, Renata; Crotti, Antônio E. M. (Associação Brasileira de Horticultura, 2015)
Bemisia tabaci (Hemiptera: Aleyrodidae) biotype B is one of the most limiting pests of tomato crops in the world. Tomato yield is currently dependent on the use of pesticides, which are problematic to farmers, consumers and the environment. A promising alternative to reduce the harmful effects caused by the indiscriminated use of synthetic insecticides is the use of insecticides of botanical origin. This study aimed to evaluate the effect of 3% (w/v) aqueous extracts from different structures of thirteen botanical species on the behavior of B. tabaci biotype B adults, as well as insecticidal activity of such aqueous extracts on B. tabaci eggs, nymphs, and adults infesting tomato plants. A distilled water solution was used as a negative control, and thiamethoxam insecticide (18 g/100 L of water) as a positive control. Leaf extract of Toona ciliata was observed to have the most efficient inhibitory effect in tests of extracts on whitefly behavior. Furthermore, the use of leaf extract of Toona ciliata led to the most drastic reduction in the number of adults and eggs on tomato leaflets. Leaf extract of Piper aduncum led to the greatest observed ovicidal effect (78.00% of non-hatched nymphs); however it was not effective against nymphs and adults. The leaf extracts of Trichilia pallida, Trichilia casaretti, and Toona ciliata showed the highest control indexes (67.9, 60.3, and 55.1%, respectively). For adults mortality, T. pallida was the most effective (72.8%). Our results indicate that application of extracts of T. pallida, T. ciliata, and T. casaretti are promising strategies to manage B. tabaci biotype B on tomato.

Bemisia tabaci (Hemiptera: Aleyrodidae) biótipo B é uma das mais limitantes pragas do tomateiro no mundo. A produção do tomateiro é altamente dependente de inseticidas, ocasionando problemas ao produtor, consumidor e ambiente. Uma alternativa promissora para redução dos efeitos maléficos ocasionados pelo uso indiscriminado de inseticidas sintéticos são os inseticidas de origem botânica. Este trabalho objetivou avaliar o efeito de extratos aquosos a 3% (p/v) de diferentes estruturas de treze espécies botânicas no comportamento dos insetos adultos de B. tabaci biótipo B bem como sua atividade inseticida sobre ovos, ninfas e adultos do inseto em tomate. A água destilada foi utilizada como controle negativo e o inseticida tiametoxam (18 g/100 L de água) como controle positivo. O extrato à base de folhas de Toona ciliata foi o mais eficiente nos testes em que foram avaliados o efeito dos extratos sobre o comportamento da mosca-branca, diminuindo o número de insetos adultos e ovos em folíolos de tomateiro. O extrato de folhas de Piper aduncum apresentou o maior efeito ovicida (78,00% de ninfas não eclodidas), no entanto foi pouco efetivo sobre ninfas e adultos. Os extratos de folhas de Trichilia pallida, Trichilia casaretti e Toona ciliata apresentaram os maiores índices de controle (67,9; 60,3; 55,1%, respectivamente). Para adultos, T. pallida foi o mais eficiente (72,8%). Com base nos resultados, a aplicação dos extratos de T. pallida, T. ciliata e T. casaretti mostra-se promissora no manejo de infestações de B. tabaci biótipo B em tomateiro.
Extratos botânicos: controle alternativo para o manejo de mosca-branca em tomateiro
Keywords: Bemisia tabaci; Solanum lycopersicum; Hemiptera; extratos aquosos.; Bemisia tabaci; Solanum lycopersicum; Hemiptera; aqueous extracts.